Quercetin-loaded nanocomposite microspheres for chronologically promoting bone repair via synergistic immunoregulation and osteogenesis. (October 2022) - Han, Chunyu; Guo, Min; Bai, Jianfei; Zhao, Lanlan; Wang, Liqiang; Song, Wenzhi; Zhang, Peibiao
Graphical abstract: Highlights: Quercetin-loaded microspheres with "eyeball-like" morphology were prepared by airflow shearing method. The encapsulation efficiency of quercetin-loaded microspheres reached nearly 80%, and possessed sustained release behavior. The quercetin-loaded microspheres promoted osteogenesis via modulating macrophage M2 polarization in the co-culture system. The quercetin-loaded microspheres displayed excellent immunoregulation and bone repair in vivo. Abstract: Biomaterial implantation for bone defect repair is a complex cascade reaction process, which mainly includes early inflammatory response and subsequent osteogenic repair. In this work, quercetin / nano-hydroxyapatite / poly (glycolide- co -epsilon-caprolactone) (Que/ n -HA/PGCL) nanocomposite microspheres were successfully prepared by airflow shearing method, possessing interconnected porous structure with unique "eyeball-like" surface morphology. The encapsulation efficiency of microspheres reaches as high as 80 % and Que release was stable and continuous, only released 7.5 % at 120 h in the 4 wt% group. Moreover, Que-loaded microspheres triggered positive immunomodulation via upregulation of M2 macrophage polarization evidenced by decreased expression of pro-inflammatory cytokines TNF-α, iNOS and the increased expression of anti-inflammatory cytokines Arg1, IL-10 in RAW264.7 cells, which was beneficial to BMSCs osteogenic differentiation in the co-culture system. Meanwhile, the capability to directly promote osteo-differentiation was manifested by upregulation of Runx2, ALP, OPN, OCN gene expression and the increase of differentiation markers. Furthermore, the assessment of Que/ n -HA/PGCL microspheres in vivo confirmed desirable bone repair contributed to efficient immunomodulation and excellent osteo-differentiation. Thus, the Que/ n -HA/PGCL microspheres could serve as potential functional filling materials for bone repair, which could be applied to efficient drug delivery platform in the future clinical applications.